Analisis Perencanaan Lokasi Gudang untuk Meminimasi Biaya Distribusi - Suryana, Hendy; Patra, Oviyan (Universitas Suryakancana, 2023)
Transportation and distribution is one aspect that is very important in influencing the success of a company in order to be able to survive and compete against other companies. In general, transportation problems are related to determining the distribution of a product from a source to several destinations with a certain demand. CV Aneka Ragam, which is a distributor company in the sale of multifunctional spray paint products to meet automotive needs in Indonesia, which is currently consumer-oriented. The most common locating problem is finding the best location from one or more warehouse points from several possible locations to achieve the lowest CV delivery cost. Aneka Ragam is the sole distributor in Indonesia that distributes Sapporo Ultimate Spray paint products to various resellers. Determining the optimal warehouse location and obtaining the right distribution warehouse area in the marketing area is carried out using the center of gravity method. The new warehouse alternative location obtained using the center of gravity method. For the warehouse location on the island of Sumatera, it is located in the Bangkinang Plaza area Blok R A 09, Jl. Sisingamangaraja, Bangkinang, Kec. Bangkinang, Kampar Regency, Riau 2846. The warehouse location on the island of Kalimantan is located in the Gang Buntu area, Jl. Banyan, Lanjas, Central Teweh, Barito Regency, Central Kalimantan 73812. The warehouse location on Sulawesi Island is located in the Benteng area, East Wara, Palopo City, South Sulawesi. The warehouse location on Nusa Tenggara Island is located in the Sukamulia area, West Lombok, Nusa Tenggara. For warehouse locations on Maluku & Papua islands, they are located in the Fak-fak area, North Wagom, Fakfak, Fakfak City, West Papua 9865. The optimal warehouse point can be produced in each region, because the warehouse point that has been determined refers to the needs of the goods requested by the customer. resellers in the city of the region and easy access to delivery of goods.Â Â Transportasi dan distribusi merupakan salah satu aspek yang sangat penting dalam mempengaruhi keberhasilan suatu perusahaan agar mampu bertahan dan bersaing terhadap perusahaan lainnya. Pada umumnya, masalah transportasi berhubungan dengan penentuan pendistribusian suatu produk dari sumber menuju beberapa tujuan dengan permintaan tertentu. CV Aneka Ragam merupakan perusahaan distributor tunggal dalam penjualan produk cat semprot Sapporo Ultimate dan menyalurkan produk cat Semprot ke berbagai reseller untuk memenuhi keperluan otomotif di Indonesia. Masalah penentuan lokasi yang paling umum adalah menemukan lokasi terbaik dari satu atau lebih titik gudang dari beberapa lokasi untuk mencapai biaya pengiriman terendah. Penentuan lokasi gudang yang optimal dan memperoleh wilayah gudang pendistribusian yang tepat di area pemasaran dilakukan dengan menggunakan metode center of gravity. Lokasi alternatif gudang baru yang diperoleh untuk gudang di Pulau Sumatera (Plaza Bangkinang Blok R A 09, Jl. Sisingamangaraja, Kabupaten Kampar, Riau), lokasi gudang di Pulau Kalimantan (Jl. Beringin, Lanjas, Kabupaten Barito, Kalimantan Tengah), lokasi gudang di Pulau Sulawesi (Benteng, Wara Timur, Kota Palopo, Sulawesi Selatan), lokasi gudang di Pulau Nusa Tenggara (Sukamulia, Lombok Barat, Nusa Tenggara), lokasi gudang di Pulau Maluku & Papua (Fak-fak, Papua Barat). Titik gudang dapat dihasilkan yang optimal di setiap wilayahnya, karena titik gudang yang telah ditentukan mengacu kepada kebutuhan barang yang diminta oleh reseller di kota wilayah tersebut dan kemudahan akses pengiriman barang.Â